Pityriasis versicolor of the face in an adult. - Chieco, P. (European Journal of Pediatric Dermatology, 2013)
In addition to genetic factors pityriasis versicolor is influenced by climatic and seasonal changes and by the age. In tropical areas the prevalence stands at around 40% of the population (1), while in cold climates falls to 1%; in the temperate areas adulthood is the most affected age starting from the puberty, while children and the elderly are less frequently affected (2). In temperate areas the disease recurs almost always at the end of the summer and sometimes at the end of the spring. The subject’s age affects not only the prevalence of the disease, but especially the distribution of the lesions. While in the adulthood the region most frequently affected is the upper part of the trunk and the root of the upper limbs, in the prepubertal age clearly prevails the involvement of the face, especially of the forehead and the parotid region. The simultaneous presence of the adult and childhood pattern of distribution is the peculiarity of our case.